The 15° reverse Trendelenburg position can improve visualization without impacting cerebral oxygenation in endoscopic sinus surgery—A prospective, randomized study. Issue 6 (7th December 2020) - Yang, Wenjing; Wang, Guyan; Li, He; Yan, Xing; Ren, Yaoyao; Wang, Yue; Hu, Haili; Song, Xiaoli; Wan, Ying; Wang, Chengshuo; Lou, Hongfei; Huang, Qian; et al.
Abstract : Background: In this study we compared intraoperative bleeding and regional cerebral oxygenation in patients with different degrees of the reverse Trendelenburg position (RTP) during endoscopic sinus surgery (ESS). Methods: In total, 120 patients with chronic rhinosinusitis treated by ESS were randomly assigned to the following 4 groups: a horizontal position (HP) group, and 5°, 10°, and 15° RTP (5‐RTP, 10‐RTP, and 15‐RTP, respectively) groups. The primary outcome was the Boezaart grading scale (BS). The cerebral oxygen saturation (ScO2 ), total blood loss, numerical rating scale (NRS) scores, and complications were also recorded. Results: The median BS values in the HP, 5‐RTP, 10‐RTP, and 15‐RTP groups were 2.0, 2.0, 2.1, and 1.7, respectively. Multiple pairwise comparisons of the BS showed significant differences between the 15‐RTP group and the other 3 groups (HP, 5‐RTP, and 10‐RTP). Regarding the NRS and bleeding rate, significant differences were found between the HP and 15‐RTP groups. No difference was found in ScO2 among the 4 groups, and no cerebral desaturation events occurred in any group. No complications, including vital organ (heart, brain, and kidney) dysfunction problems, were reported in this study during hospitalization. Conclusion: Compared with HP, 5‐RTP, and 10‐RTP, 15‐RTP can improve visual clarity during ESS, and ScO2 is not affected by the degree of RTP. No cerebral deoxygenation or vital organ dysfunction was observed in this study. Therefore, we recommend 15‐RTP with moderate deliberate hypotension for ESS.